Manual sobre cuidado nutricional em pacientes com feridas crônicas para profissionais de saúde - Alves, Paula Pens [UNIFESP] (2019)
Introduction: The follow-up of patients with wounds and healing disorders is fundamental, since the healing process is complex and dependent on the nutritional status of the patient. Objective: To develop and validate a manual on nutritional care in patients with chronic wounds for health professionals. Method: This is a descriptive study on the development and validation of a manual, conducted through bibliographic survey, content preparation, validation with expert judges using the Delphi Technique with Content Validation Index and disclosure. Results: The 38-page, 5-chapter, 46-image “Manual on Nutritional Care in Chronic Wound Patients for Healthcare Professionals” was developed and registered in the ISBN online presentation. The elaborated manual was validated by experts in two cycles by the Delphi technique. In the first cycle the Content Validation Index (CVI) was 0.90, while in the second cycle the percentage of agreement was absolute of the entire manual, with CVI of 1.00. The overall CVI was 0.95, reaching the validation target. Conclusion: The “Manual on nutritional care in patients with chronic wounds for health professionals” was developed and validated.